Figurative portraits/prints and paintings - Anderson, Douglas P., author; Orman, Jack L., advisor; Twarogowski, Leroy A., committee member; Dormer, James T., committee member (Colorado State University. Libraries, 1992)
The human figure possesses all the forms, lines and shapes found in nature. What differentiates it from inanimate objects is that it also possesses a spirit and psychological presence. It is for this reason I choose to work with the human figure. My reaction to the model is very important but the model's response to me is also transposed into my work. It is important that I approach my work honestly and without hesitation and preconceptions. For me the act of drawing becomes the Art. It can be a trance-like experience and sometimes the results will surprise me. At all times the likeness of the model is secondary. The print medium, as an extension of my drawing, presents a challenge that I find appealing. There is always present the problem of keeping images alive and fresh while at the same time controlling the technical aspects of the print process. I find that the intaglio techniques are a way for me to continue my exploration of the human figure in a way that is rich and vital.
Keywords: Figurative art; Human figure in art